Prefabricated Press-Formed Steel T-Box Girder Bridge System - Taly, Narendra; GangaRao, H.V.S. (Engineering Journal, 1979)
The conventional bridge construction methods are time consuming and costly because of the high costs of material and labor. In addition, bridge maintenance costs are increasing rapidly. Hence, the need for more economical techniques of rehabilitating existing bridges and building new ones is well recognized. To this end, several innovative modular bridge systems are being developed by the authors and have been reported in the literature. This paper presents the details of an all-steel superstructure system that is economical and suitable for span ranges of 40 to 100 ft under HS20-44 loading. Herein, it is referred to as the press-formed prefabricated steel box girder-bridge system.